Raman spectroscopy - Goh, P. S. (Elsevier Inc., 2017)
Raman spectroscopy is a valuable tool for qualitative and quantitative polymeric membrane characterization. The interactions among the functional groups, chain orientation, structural changes upon treatment/modification, and interfacial properties of the polymeric composite are some of the interesting information that can be revealed from the Raman spectra. This chapter presents the principle of Raman spectroscopy and its applications for the characterization of polymer materials, particularly polymeric membranes. The utilization of Raman spectroscopy to provide valuable understanding of chemical and physical properties for further development of advanced and novel polymeric membranes is highlighted.